Perhitungan Dana Tabarru’ Asuransi Syariah Menggunakan Hukum Mortalita Makeham dengan Metode Cost of Insurance - Riri Indriani; Devni Prima Sari (Journal of Mathematics UNP, 2020)
Abstract  — Tabarru’ funds in Islamic insurance is a number of funds that are used to help each other between insurance participants. In the fund management mechanism with savings element, Tabarru’ funds have a percentage of payment of 5%. Whereas in the management of funds without savings, it is not known how much the percentage must be paid to the company, so that it will cause confusion for customers. In this research, we will discuss how to calculate the tabarru’ funds using the cost of insurance method. This calculation involves the probability of death based on the Makeham mortality table. Makeham Mortality Tables can be arranged by estimating parameters using the least squares method. obtained parameters A, B and C, respectively for men, namely 0.05822, 0.00158 and 1.08394, while for women namely 0.04418, 0.00152 and 1.08400. So the amount of tabarru’ funds  that must be paid by someone aged x that is,Keywords — Tabarru’ funds, Makeham Mortality Law, Least Squares Method, Cost of Insurance Method